Publisher Correction: Flexible Learning-Free Segmentation and Reconstruction of Neural Volumes. Issue 1 (December 2018) - Shahbazi, Ali; Kinnison, Jeffery; Vescovi, Rafael; Du, Ming; Hill, Robert; Joesch, Maximilian; Takeno, Marc; Zeng, Hongkui; Costa, Nuno; Grutzendler, Jaime; Kasthuri, Narayanan; Scheirer, Walter
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.